Spinal processing of somatosensory information in the developing dorsal horn - Battell, Emma Elizabeth (2022)
Somatosensory processing is immature at birth and significant changes occur during postnatal development throughout the neuroaxis, which produce mature processing of these sensory modalities. There is increasing evidence that disruptions to normal development are associated with an increased risk of developing pain-related conditions in adulthood. As the spinal dorsal horn is a key integrative centre in the somatosensory system, fully understanding how the processing of peripheral stimulation matures at this site is undoubtedly beneficial. Previous research into postnatal maturation of the physiological responses of the dorsal horn predominantly relied upon single-unit electrophysiology and has demonstrated multiple critical periods of development over the first four postnatal weeks in rats. However, as the dorsal horn is very heterogeneous, with distinct roles for each of the laminae, we propose that investigating the development of the whole dorsal horn requires a broader approach which is not achievable from just measuring the activity in single neurons. Therefore, the aim of this thesis was to use spinal multielectrode array (MEA) electrophysiology, developed in our laboratory, in postnatal rats. This would enable the simultaneous study of all laminae of the dorsal horn across postnatal development, but also in rats which are older than those normally used in pre-clinical pain research, allowing changes across the whole life course to be investigated.